A study on the relationship between work life balance and job performance among employees at Majlis Daerah Bera / Farina Hafiza Mohd Fadil - Mohd Fadil, Farina Hafiza (2016)
The purpose of this report to show the information during the industrial practical and the project that study in the organization. The background of the company that students do their practical and what they do in period of practical in Majlis Daerah Bera. The project that the student carry out was E-Ietter system in the organization. This is because from the observation and practical study it shown that the problem facing in handling the mail. Since in the Human Resources and Management they need to handle all of the mail to the 6 other departments in Majlis Daerah Bera. Thus, the mails come in large quantity per day. study is to identify the relationship between work life balance and job performance among employees at Majlis Daerah Bera. This study investigates three dimensions or work life balances which are workload, working hours, work family conflict and job performance. The questionnaires had been distributed convenience sampling to the employees in Department of Management Services. This departments have three unit all together which are Administration and Human Resources Unit, Enforcement Division Unit and Information Technology Unit. The respondents for this study were 52 respondents based on Krejcie & Morgan table for a given population. After collected the questionnaires from the respondents, the data had been analysed by using Statistical Package For The Social Sciences (SPSS) version 20 to get the results.